Genome screening for reducing type I polyketide synthase genes in tropical fungi associated with medicinal plants - Juangjun Jumpathong (2018)
The aim of this work was to employ primers, which encode ketosynthase (KS) domains designed to detect Lovastatin-type PKSs (highly reduced molecules), to identify fungal species that have the potential for polyketide production. Using this strategy we have identified twenty-three KS sequences from twenty different fungal strains associated with medicinal plants found in Thailand. Phylogenetic analysis based on these sequences suggested that rapid screening provided the potential to explore significant PKS structural diversity. With this primer set a unique subclade of reducing type I PKS was identified. This encodes uncharacterized functional enzyme systems, which may suggest a novel function for these pks. Two fungi, Eupenicillium shearii and Myrothecium pandanicola within this novel clade, were investigated for polyketide synthesis. Three compounds, p-hydroxyphenopyrrozin (1) phenopyrrozin (2), and 2,3-dihydro-5-methoxy-2-methylchromen-4-one (3), were identified. © 2011 Springer Science+Business Media B.V.